The two eyes of the Earth : art and ritual of kingship between Rome and Sasanian Iran - Canepa, Matthew P., 1975- (Transformation of the classical heritage, 2009)
This pioneering study examines a pivotal period in the history of Europe and the Near East. Spanning the ancient and medieval worlds, it investigates the shared ideal of sacred kingship that emerged in the late Roman and Persian empires. This shared ideal, while often generating conflict during the four centuries of the empires' coexistence (224-642), also drove exchange, especially the means and methods Roman and Persian sovereigns used to project their notions of universal rule: elaborate systems of ritual and their cultures' visual, architectural, and urban environments. Matthew Canepa expl.